Kernel L-Ideals and L-Congruence on a Subclass of Ockham Algebras - Teferi Getachew Alemayehu; Derso Abeje Engidaw; Gezahagne Mulat Addis (Journal of Mathematics)
In this paper, we study L-congruences and their kernel in a subclass Kn,0 of the variety of Ockham algebras A. We prove that the class of kernel L-ideals of an Ockham algebra forms a complete Heyting algebra. Moreover, for a given kernel L-ideal ξ on A, we obtain the least and the largest L-congruences on A having ξ as its kernel.